Analisis Pengaruh Pendidikan dan Pendapatan Perempuan Muslim Terhadap Tingkat Kemiskinan Jawa Timur - Fisabilillah, Ladi Wajuba; Baiduri, Almas (Universitas Negeri Surabaya, 2022)
Poverty is a crucial multidimensional problem in various regions, including in East Java. East Java has the highest poverty rate in Indonesia, making it the poorest province in the country. Seeing as this number is in accordance with Nurske's theory, this poverty influences each other in various aspects, one of which is education. Becker's theory shows that other things that affect poverty is household sector. Women's income contribution has the potential to cause families to live above the poverty line. The purpose of this study was to analyze the effect of women's education level and income contribution to poverty in East Java for the 2011–2021 period. This study uses 11 variables, education and women's income contribution as independent variables, and poverty in East Java as the dependent variable. The research model was analyzed using the OLS regression technique. The results of the study prove that the level of education among women has no effect on poverty. Because women's education is one of the long-term investments in national development. Meanwhile, the contribution of women's income has a negative effect on poverty. The greater the income contribution of women in the family, the greater the chance of living above the poverty line.